Saffron (Crocus sativus) and its constituents in ovalbumin-induced asthma model: a preclinical systematic review and meta-analysis - Ghobadi, Hassan; Aslani, Farzin; Boskabady, Mohammad Hossein; Saadat, Saeideh; Aslani, Mohammad Reza (Frontiers in Pharmacology, 2024)
Animal and human studies have demonstrated that the saffron and the active components of saffron, including crocin, crocetin, and safranal, possess anti-inflammatory, antioxidant, and immunomodulatory properties. In this meta-analysis, the preclinical evidence and potential mechanism of saffron were explored in an animal model of ovalbumin-induced asthma.Methods: Studies related to saffron and its constituents in an animal model of ovalbumin-induced asthma from the beginning to March 2024 were searched from Scopus, PubMed, and Web of Science databases. The methodological quality of the studies was evaluated using the 15-item CAMARADES checklist. Data analysis was performed using Comprehensive Meta-Analysis (CMA) software version 2.Results: Thirteen studies with 536 animals (268 animals in the intervention group and 268 animals in the ovalbumin-induced group) were analyzed. The meta-analysis findings demonstrated that saffron and its constituents played a significant role in reducing total WBC, eosinophil, lymphocyte, and monocyte counts. Moreover, saffron showed a significant decrease in the levels of IL-4, IL-5, IL-13, IgE, histamine, endothelin, nitric oxide, and nitrite. Moreover, saffron was found to elevate EC50 thresholds and lower maximum response rates in experimental animals.The analysis revealed a significant identification of modulation in endoplasmic reticulum (ER) stress markers and miRNAs pathways.Saffron and its components may impact ovalbumin-induced asthma model in animals through anti-inflammatory, antioxidant, and immunomodulatory pathways, as well as improving pulmonary function and modulating ER stress markers and miRNAs pathways. As a result, saffron should be considered for further clinical trials in individuals suffering from asthma.